Potensi Biomassa dan Karbon Vegetasi Hutan Rawa Gambut di Petak Ukur Permanen Hutan Pendidikan Hampangen Universitas Palanka Raya Kalimantan Tengah: Potency of Biomass and Carbon Vegetation of Peat Swamp Forest in The Permanent Sample Plot The Hampangen Educational Forest, Palangka Raya University, Central Kalimantan - Yanarita; Nuwa; Johanna Maria Rotinsulu; Ajun Junaedi; Robby Octavianus (HUTAN TROPIKA, 2021)
The purpose of this study (a) determine the composition and structure of vegetation based on the growth rate (tree, pole, sapling, seedling) in each Permanent Sample Plot (PSP); (b) to calculate the potency of biomass and carbon in vegetation trees level, poles and sapling on each PSP. The results showed that the number of vegetation species found in PSP-1 as many as 47 species with 28 family and PSP-2 of 33 species with 24 family. The vegetation of species that dominate based on the level of growth (tree, pole, sapling, seedling) in the PSP-1 consists of : Gerunggang (Cratoxylum arborescens (Vahl) Blume) and Jambu-jambu (Syzigium sp). In PSP-2 of vegetation species that dominance Tumih (Combretocarpus rotundatus (Miq.) Danser) and Jambu-jambu (Syzigium sp). The structure of the vegetation horizontally in the PSP-1 and PSP-2 dominated the vegetation of the small diameter and structure of the vegetation vertical in the dominance of vegetation including the stratum D. The average value the species diversity indexs vegetation tree level, pole, sapling and seedling in PSP-1 at 2.09 included in the category of “medium” and in PSP-2 of 1.83 which is included in the category of “low”. The potency vegetation biomass total in PSP-1 and PSP-2 respectively 152.69 tons/ha and 122.93 tons/ha as well as the potency carbon vegetation total in PSP-1 and PSP-2 respectively 71.76 tons/ha and 57.78 tons/ha.